Natural autoantibodies and their functional therapeutic roles in intravenous immunoglobulin - Danieli, Maria Giovanna; Claudi, Ilaria; Buti, Elena; Gammeri, Luca; Gangemi, Sebastiano; Shoenfeld, Yehuda Julyus (Frontiers in Aging, 2025)
Natural autoantibodies (NAbs) are a key component of the immune system, produced mainly by B-1 cells without prior antigenic stimulation. These antibodies exhibit broad reactivity toward both self and non-self antigens and contribute to immune homeostasis by clearing apoptotic cells and cellular debris, modulating immune responses, preventing autoimmune reactions, and promoting tissue repair. NAbs are present in intravenous immunoglobulin (IVIg) preparations, where they play an important role in the therapeutic effects observed in autoimmune, inflammatory, and neurodegenerative diseases. Importantly, NAbs of the IgG class contained in commercial IVIg originate from large-scale pooling of sera from thousands of healthy donors, and are recovered after multiple enrichment and purification steps during the manufacturing process. This review provides a comprehensive overview of the physiological functions of NAbs and their involvement in the mechanisms of action of IVIg. The review particularly focuses on anti-idiotypic antibodies within IVIg, which can neutralize pathogenic autoantibodies in diseases such as systemic lupus erythematosus, antiphospholipid syndrome, and pemphigus vulgaris. In the neurological field, NAbs in IVIg have been shown to target misfolded proteins such as amyloid-beta and alpha-synuclein, reduce neuroinflammation, and support neuronal survival, with promising results in Alzheimer’s disease, Parkinson’s disease, autoimmune encephalitis, and small fiber neuropathy. Similarly, in dermatological and systemic autoimmune diseases, NAbs contribute to immune regulation and the neutralization of tissue-damaging autoantibodies. Enhancing the therapeutic potential of IVIg through selective enrichment of beneficial NAb subsets could represent a promising direction for future research aimed at improving outcomes in a wide range of immune-mediated diseases.